2017
DOI: 10.1007/s40415-017-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of spiked pepper, Piper aduncum L. (Piperaceae), for the control of caterpillar soybean looper, Chrysodeixis includens Walker (Lepidoptera: Noctuidae)

Abstract: The resistance of pests to insecticides and the high costs of pest control have prompted a search for less harmful alternatives to the environment. Phytoinsecticides can be a promising option in the control of pests. The insecticidal properties of the essential oil of Piper aduncum L. (Piperaceae) have been demonstrated by several authors. This study was aimed at evaluating the insecticidal activity of P. aduncum essential oil on caterpillars of the soybean looper, Chrysodeixis includens Walker. Two bioassays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Piper genus essential oil has exhibited promising results in pest control, because of active compounds, as terpenoid and phenylpropanoid that are broadly knowledge by toxicity on arthropods pest (Fazolin et al, 2007;Scott et al, 2007;Boulogne et al, 2012;Regnault-Roger et al, 2012), included to lepidopterans pest (Lima et al, 2009;Sanini et al, 2017). In addition, these compounds has been reported by exhibit low toxicity on egg parasitoids, which makes possible integrate with biological control (Turchen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Piper genus essential oil has exhibited promising results in pest control, because of active compounds, as terpenoid and phenylpropanoid that are broadly knowledge by toxicity on arthropods pest (Fazolin et al, 2007;Scott et al, 2007;Boulogne et al, 2012;Regnault-Roger et al, 2012), included to lepidopterans pest (Lima et al, 2009;Sanini et al, 2017). In addition, these compounds has been reported by exhibit low toxicity on egg parasitoids, which makes possible integrate with biological control (Turchen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the chemical compounds present in these Piperaceae can be further evaluated among the isolation of active molecules to develop new botanical formulations, especially when we consider that the majority of these substances has been reported as potential insecticides in many other studies conducted worldwide (Santos et al, 2010;2013;Cáceres & Kato, 2014, Brito, Baldin, Silva, Ribeiro, & Vendramim, 2015Krinski & Foerster, 2016, Sanini et al 2017, Turchen, Hunhoff, Paulo,Souza, Pereira, 2016b and other plant families (Isman, 2000;Koul, Walia, & Dhaliwal, 2008;Tripathi, Upadhyay, Bhuiyan, & Bhattacharya, 2009;Coitinho, Oliveira, Gondim-Júnior, & Câmara, 2010;Ntalli & Menkissoglu-Spiroudi, 2011, Zoubiri & Baaliouamer, 2011Baskar, Muthu, Raj, Kingsley, & Ignacimuthu, 2012;Krishnappa & Elumalai, 2012;Cáceres & Kato, 2014Krinski, Massaroli, & Machado, 2014;Backiyaraj et al, 2015;Massaroli, Pereira, & Foerster;Costa, Santana, Oliveira, & Serrão, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the leaves of P. cachimboense are easily harvested, the species is a good candidate for bioactivity testing of its oils regarding pest control in its occurrence region (Krinski 2013;Krinski 2015;Krinski et al 2015;Krinski and Foerster 2017), as already known for other Piperaceae species (Krinski and Foerster 2016;Turchen et al 2016;Sanini et al 2017). …”
Section: Amazonicamentioning
confidence: 99%